2018
DOI: 10.1016/j.physletb.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of angular parameters from the decay B0 → K⁎0μ+μ− in proton–proton collisions at s=8TeV

Abstract: Angular distributions of the decay B 0 → K * 0 µ + µ − are studied using a sample of proton-proton collisions at √ s = 8 TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb −1 . An angular analysis is performed to determine the P 1 and P 5 parameters, where the P 5 parameter is of particular interest because of recent measurements that indicate a potential discrepancy with the standard model predictions. Based on a sample of 1397 signal events, the P 1 and P 5 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 62 publications
6
109
0
Order By: Relevance
“…A key application of the refined SM prediction for ∆M s is in the context of the recent hints of lepton flavour universality (LFU) violation in semi-leptonic B meson decays. Focussing on neutral current anomalies, the main observables are the LFU violating [40][41][42], together with the angular [43][44][45][46][47][48][49][50][51][52] and the branching ratios of hadronic b → sµ + µ − decays [43,44,53]. The effective Lagrangian for semi-leptonic b → sµ + µ − transitions contains the terms…”
Section: Status and Future Prospects Of The B → S Anomaliesmentioning
confidence: 99%
“…A key application of the refined SM prediction for ∆M s is in the context of the recent hints of lepton flavour universality (LFU) violation in semi-leptonic B meson decays. Focussing on neutral current anomalies, the main observables are the LFU violating [40][41][42], together with the angular [43][44][45][46][47][48][49][50][51][52] and the branching ratios of hadronic b → sµ + µ − decays [43,44,53]. The effective Lagrangian for semi-leptonic b → sµ + µ − transitions contains the terms…”
Section: Status and Future Prospects Of The B → S Anomaliesmentioning
confidence: 99%
“…In particular b → sℓ þ ℓ − transitions seem to be in tension with the SM expectations: branching ratios of hadronic b → sμ þ μ − decays [1][2][3] and the angular distributions for B → K ðÃÞ μ þ μ − decay [2][3][4][5][6][7][8][9][10][11] hint at a negative, beyond the SM (BSM) contribution to C 9 [12][13][14][15][16][17][18][19][20][21][22][23]. The significance of the effect is still under discussion because of the difficulty of determining the exact size of the hadronic contributions (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The theory approach to inclusive FCNC decays is in this sense somewhat different compared to exclusive ones; in particular, the underlying hadronic uncertainties in inclusive modes are largely independent of those in exclusive transitions. Hence, one useful way to shed light on the nature of the anomalies currently outstanding in exclusive B decays at various experiments [3][4][5][6][7][8][9][10][11][12][13][14][15] is a cross-check via the corresponding observables in the inclusive modes. Indeed, a study on the combined new-physics sensitivity clearly revealed the synergy and complementarity of exclusive versus inclusive FCNC decays [16].…”
Section: Introductionmentioning
confidence: 99%